Performance of UNHCR nutrition programs in post-emergency refugee camps - Wilkinson Caroline; Haskew Christopher; Tappis Hannah; Doocy Shannon; Spiegel Paul (Conflict and Health, 2011)
Abstract Background The United Nations High Commissioner for Refugees (UNHCR) launched a health information system (HIS) in 2005 to enhance quality and consistency of routine health information available in post-emergency refugee camps. This paper reviews nutrition indicators and examines their application for monitoring and evaluating the performance of UNHCR nutrition programs in more than 90 refugee camps in 18 countries. Methods The HIS is a primary source of feeding program data which is collected using standardized case definitions and reporting formats across refugee camps in multiple settings. Data was aggregated across time periods and within and across countries for analysis. Basic descriptive statistics were then compared to UNHCR program performance standards. Results Camp populations covered by the HIS ranged from 192,000 to 219,000 between 2007 and mid-2009; 87% of under five children covered by the HIS were in Africa and 13% in Asia. Average moderate acute malnutrition (MAM) and severe acute malnutrition (SAM) rates reported in 74 of 81 camps for the 2007-2009 time periods were 7.0% and 1.6%, respectively. The supplementary feeding program (SFP) admission rate was 151/1000/yr with 93% of SFP admissions occurring in Africa. SFP performance consistently exceeded all UNHCR standards with the exception of length of enrollment. Average length of SFP enrollment was 12 weeks in Africa and 22 weeks in Asia as compared to the UNHCR standard of < 8 weeks. The therapeutic feeding program (TFP) admission was 22/1000/yr with 95% of TFP admissions in Africa. TFP performance met UNHCR standards with the exception of daily weight gain. Conclusions Inclusion of children identified as moderately and severely wasted in the HIS would allow UNHCR to better track and respond to changes in nutrition status. Improved growth monitoring coverage or active malnutrition surveillance would increase UNHCR's ability to identify and treat cases of acute malnutrition. Expansion of nutrition reporting to address the transition to community-based therapeutic care is essential for adequate performance monitoring in the future. In terms of program priorities, a focus on camps and countries with large refugee populations and high feeding program enrollment rates would have the greatest impact in terms of absolute reductions in the incidence and prevalence of malnutrition.